2020
DOI: 10.1111/add.15249
|View full text |Cite
|
Sign up to set email alerts
|

The impact of survey mode on US national estimates of adolescent drug prevalence: results from a randomized controlled study

Abstract: Background and Aims Increasing numbers of school‐based drug surveys are transitioning data collection to electronic tablets from paper‐and‐pencil, which may produce a survey mode effect and consequent discontinuity in time trends for population estimates of drug prevalence. This study tested whether (a) overall, self‐reported drug use prevalence is higher on electronic tablets versus paper‐and‐pencil surveys, (b) socio‐demographics moderate survey mode effects and (c) levels of missing data are lower for elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…A US Centers for Disease Control and Prevention web-based survey suggested that many adults used substances to cope with COVID-19–related stress, but no corresponding information was provided about possible reductions in substance use . Most recently, Monitoring the Future data from students queried in January to June 2021 showed broad declines across nearly all substances for 8th, 10th, and 12th grade students (approximately ages 13-14, 15-16, and 17-18 years), results which were consistent with our findings for teenaged participants in the PATH Study, interviewed in July to December 2020 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A US Centers for Disease Control and Prevention web-based survey suggested that many adults used substances to cope with COVID-19–related stress, but no corresponding information was provided about possible reductions in substance use . Most recently, Monitoring the Future data from students queried in January to June 2021 showed broad declines across nearly all substances for 8th, 10th, and 12th grade students (approximately ages 13-14, 15-16, and 17-18 years), results which were consistent with our findings for teenaged participants in the PATH Study, interviewed in July to December 2020 …”
Section: Discussionsupporting
confidence: 86%
“… 14 Most recently, Monitoring the Future data from students queried in January to June 2021 showed broad declines across nearly all substances for 8th, 10th, and 12th grade students (approximately ages 13-14, 15-16, and 17-18 years), results which were consistent with our findings for teenaged participants in the PATH Study, interviewed in July to December 2020. 15 …”
Section: Discussionsupporting
confidence: 78%
“…Similarly, school closings during COVID-19 have jeopardized the ability of those conducting Monitoring The Future (MTF; an annual national survey on drug use conducted in school classrooms) to collect data in person. COVID-19 will likely trigger a swift switch to web-based surveys, and researchers have already initiated studies to assess comparability of results using different data collection methods ( Miech et al, 2020 ). Additionally, researchers need approaches to better cover hard-to-reach populations (e.g., incarcerated or homeless) or those without internet access, and data collection methods that are more timely and representative of the population and that combine multiple modalities.…”
Section: Epidemiologymentioning
confidence: 99%
“…Prior studies of survey administration mode effect have found computer‐assisted and web‐delivered administration of school‐based surveys yielded results that were largely equivalent to traditional paper‐and‐pencil survey results 2‐5 . While some studies have shown differences in prevalence estimates for less socially desirable behaviors, eg, sexual behavior and substance use, 6‐8 a clear mode effect for sensitive risk behaviors has not been consistently reproduced in other studies 9‐11 . To gain a more comprehensive understanding of the potential impact of survey administration mode, other studies have explored measures in addition to prevalence estimates, including percent nonresponse, 4 percent of specific subject questions answered, 9,12 and time to complete survey 12 .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] While some studies have shown differences in prevalence estimates for less socially desirable behaviors, eg, sexual behavior and substance use, [6][7][8] a clear mode effect for sensitive risk behaviors has not been consistently reproduced in other studies. [9][10][11] To gain a more comprehensive understanding of the potential impact of survey administration mode, other studies have explored measures in addition to prevalence estimates, including percent nonresponse, 4 percent of specific subject questions answered, 9,12 and time to complete survey. 12 Similarly, in this study, select metrics across a broad range of topic areas were examined to evaluate data quality and representativeness between survey administration modes.…”
mentioning
confidence: 99%